Money and Banking in Medieval and Renaissance Venice : Volume I: Coins and Moneys of Account - Lane, Frederic Chapin, 1900-1984 (Book collections on Project MUSE., 2019)
Frederic C. Lane and Reinhold C. Mueller, in the first volume of Money and Banking in Medieval and Renaissance Venice, discuss Venice's economic achievement in terms of the complex system the city's inhabitants developed to manage moneys of account and coins. Money merchants of Venice developed a system whereby a premium attached to moneys of account acted as a stabilizing force and allowed merchants to engage in long-term trade. This system, according to the authors, helped establish Venice as a dominant city-state in international trade and exchange. This book outlines the development and success of this system through 1508. At the time it was first published, this book made a significant contribution to the history of money and economics by underscoring the large role that Venice played in the economic history of the West and the ascendance of capitalism as a structuring force of society.